Magainin as an Antiviral Peptide of SARS-CoV-2 Main Protease for Potential Inhibitor: An In Silico Approach - Taufik Muhammad Fakih; Mentari Luthfika Dewi; Eky Syahroni (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2020)
The new coronavirus (SARS-CoV-2), which caused the global pandemic Coronavirus Disease-2019 (COVID-2019), has infected nearly 206 countries. There is still little information about molecular compounds that can inhibit the development of infections caused by this disease. It is crucial to discover competent natural inhibitor candidates, such as antiviral peptides, because they have a variety of biological activities and have evolved to target biochemical machinery from different pathogens or host cell structures. In silico studies will be carried out, including protein-peptide docking and protein-protein docking, to identify, evaluate, and explore the affinity and molecular interactions of the Magainin-1 and Magainin-2 peptide molecules derived from frog skin (Xenopus laevis) to the main protease macromolecule (Mpro) SARS-CoV-2, and its effect on the ACE-2 receptor (Angiotensin Converting Enzyme-2 Receptor). Protein-peptide docking simulations show that both peptide molecules have a good affinity for the active site area of the SARS-CoV-2 Mpro macromolecule. These results were then confirmed using protein-protein docking simulations to observe the ability of the peptide molecule in preventing attachment to the ACE-2 receptor surface area. In silico studies show that Magainin-2 has the best affinity, with a bond free energy value of −3054.53 kJ/mol. Then the protein-protein docking simulation provided by Magainin-2 prevented the attachment of ACE-2 receptors, with an ACE score of 1697.99 kJ/mol. Thus, through in silico research, the Magainin peptide molecule can be further investigated in the development of new antiviral peptides for the treatment of infectious diseases of COVID-19.